The Influence of Covid-19 Preparedness Through Health Care Implementation on Ship Crew - Asriwati Amirah; Teguh Suharto; Erni Yetti; Artifa Sari; Rizal Mayridian (Media Kesehatan Masyarakat Indonesia, 2021)
An increasing number of people exposed to diseases is caused by uneven public awareness of personal health and the factors that cause the infectious diseases. Meanwhile, the government has limited funds and personnel, which causes an inability to achieve maximum goals in disease prevention. Therefore, this study aims to analyze the relationship between responsiveness, reliability, empathy, assurance, and tangible aspects with patient satisfaction regarding preparedness services at Belawan Port, Medan City in 2020. The quantitative analytic survey was used with a cross-sectional design. The population used was all ship crews presented and worked on the ship when it was anchored at Light I of Belawan Port. The sample consisted of 95 crew members. Analysis of the chi-square test shows the following results: responsiveness (p=0.001), reliability (p=0.001), assurance (p=0.002), empathy (p=0.001) and physical aspect (p=0.060). The logistic regression test shows the variable that influences the most satisfying service in preparedness service is empathy, with an Exp (B) value of 4.781. The conclusion shows that responsiveness, reliability, assurance, and empathy-related to crew satisfaction, while the physical aspect has no relationship with it. It is recommended to improve the quality of preparedness services for crew members by increasing supervision and inspection, and attention to prevent disease transmission and establish a harmonious relationship between health workers and crew members for customer satisfaction.